Codex Schøyen 2650 : a Middle Egyptian Coptic witness to the early Greek text of Matthew's Gospel : a study in translation theory, Indigenous Coptic, and New Testament textual criticism - Leonard, James M., 1962- (New Testament tools, studies and documents., 2014)
James M. Leonard analyzes the very important early Coptic manuscript of Matthew's Gospel, Codex Schøyen. Through a careful translational analysis, he shows how its close alliance with Vaticanus and Sinaiticus helps identify an earlier text form which they mutually reflect.